A cebocephalus (cyclopia) monster in a non descript cow - GUPTA, K A; ANAND, T C (The Indian Journal of Animal Reproduction, 2023)
A cebocephalus monster with epitheliogenesis imperfecta over the forehead having rudimentary and fused eye balls. a typical, deformed ears and jaw was delivered in a non-descript cow by traction.